The Practice of One Territorial Jurisdiction of the Federal High Court of Nigeria and the Need for Constitutional Amendments to Decongest the Courts - Abua, Arinze; Nuagbo, Ndukauba C. (ABUAD Private and Business Law Journal, 2018)
This article reviews the decisions of the Supreme Court in Owners of M.V. Alabera v. NAIC (2008)11 NWLR (pt.1097) 182 which held that a State of Nigeria in relation to one another is outside jurisdiction of the Federal High Court of Nigeria and leave is required to issue, serve and mark as concurrent, one within and the other to be served outside jurisdiction and the recent decision of the Supreme Court that the Federal High Court has one jurisdiction means outside the Federal Republic of Nigeria in the case of Biem v. Social Democratic Party & 2ors unreported SC.341/2019. Even the issue of one jurisdiction portends a greater problem in that the courts will continue to be congested as some Federal causes are also determinable by the State High Courts and all appeals from Magistrate Courts, Customary Courts, High Courts all pass through the Court of Appeal, Customary Court of Appeal and Sharia Courts of Appeal all the way to Supreme Court. This article adopts the doctrinal approach of reviewing the cases and incidences of True Federalisms to recommend Constitutional Amendments to create state courts of Appeal and Supreme Courts to help decongest the courts and concludes that in as much as one jurisdiction problem of the Federal High Court has been clarified by the Supreme Court in Biem’s case, a lot in terms of Constitutional amendment to decongest the Court ought to be embarked upon as done in other countries such as the United States of America.